Implementation Of Education Through Multimedia Video Learning On The Understanding Of Helminth Infections - Riris Andriati; Fenita Purnama Sari Indah; Destra Trisna Romadhon (Genius Journals, 2021)
The prevalence of worm infection in Indonesia reaches 28.12%, but this is does not reflect the actual condition because there are still many areas in Indonesia that have not been covered by the worm infection examination. The objective of this study was to determine the effect of education through audiovisual methods on helminth infections in students at SDN Cipayung 2, South Tangerang City. This research method is quantitative research using Pre Experimental Design with One Group Pre test and Post test approach. The number of samples was 93 students at SDN Cipayung 2, South Tangerang City and used a total sampling technique. The results showed that there was an increase in the average value of understanding about helminth infections before and after being given counseling using the audiovisual method. The increase in the average (mean) pretest value of 30.40 increased to 40.27 in the posttest value, the pretest (median) value of 30.00 increased to 40.00 in the posttest value, the pretest (minimum) value of 17 increased to 31 on the average posttest value and the (maximum) pretest value of 39 increased to 50 on the average posttest value. Based on the results of the Paired-Sample T Test, the results obtained P Value = 0.000,. And it can be concluded that implementation of education through multimedia video learning on the understanding of helminth infections is very effective. This research will explore the effect of education through multimedia video learning on the understanding of helminth infections.
Keywords: Education; Multimedia Video Learning; Helminth Infections